(untitled) (Olhares, 2020)
This article seeks to discuss in its entirety the possibilities of the territories in which we can trigger our noisy performances. Tensioning aesthetics from the perspectives of dissident and dissonant existences, understanding that our stocks are inscribed on the territory providing a new understanding of borders. Comprehend current possibilities and political scenarios, we look at topics such as narrative disputes and new worlds, or the frontier spaces to discuss the space in which performance takes place and how our bodies fit into performance in these frontier territories.